2014
DOI: 10.1038/ismej.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Climate change affects key nitrogen-fixing bacterial populations on coral reefs

Abstract: Coral reefs are at serious risk due to events associated with global climate change. Elevated ocean temperatures have unpredictable consequences for the ocean's biogeochemical cycles. The nitrogen cycle is driven by complex microbial transformations, including nitrogen fixation. This study investigated the effects of increased seawater temperature on bacteria able to fix nitrogen (diazotrophs) that live in association with the mussid coral Mussismilia harttii. Consistent increases in diazotroph abundances and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 44 publications
6
111
0
Order By: Relevance
“…Nevertheless, the dominant associated diazotrophs may also vary depending on the health of the coral (Yang et al, 2015). Bacterial diversity decreases as corals grow, and the dominant groups also change with each life stage, likely reflecting a fine tuning of the hosted microbial community upon changes in metabolic needs in different life stages and/or when experiencing environmental stress or disease (Nissimov et al, 2009;Ceh et al, 2013b;Lema et al, 2014b;Santos et al, 2014 see Section Does Diazotrophy Enhance Coral Resilience? ).…”
Section: Diversity Of Diazotrophs In Tropical Coralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the dominant associated diazotrophs may also vary depending on the health of the coral (Yang et al, 2015). Bacterial diversity decreases as corals grow, and the dominant groups also change with each life stage, likely reflecting a fine tuning of the hosted microbial community upon changes in metabolic needs in different life stages and/or when experiencing environmental stress or disease (Nissimov et al, 2009;Ceh et al, 2013b;Lema et al, 2014b;Santos et al, 2014 see Section Does Diazotrophy Enhance Coral Resilience? ).…”
Section: Diversity Of Diazotrophs In Tropical Coralsmentioning
confidence: 99%
“…In such events, corals' resilience could be enhanced by alternative fixed nitrogen sources such as that provided by endosymbiont diazotrophs. For example, Santos et al (2014) reported that the abundance and diversity of diazotrophs associated with the coral Mussismilia harttii increase in response to +2 to +4.5 • C above in situ background seawater temperature. In the Red Sea coral-associated N 2 fixation rates have been reported to increase 3-to 10-fold when corals are artificially exposed to higher temperatures (Cardini et al, 2016b) as well as in response to natural rising temperatures in the summer, suggesting that DDN could provide alternative nitrogen sources when environmental nutrient concentrations are scarce .…”
Section: Does Diazotrophy Enhance Coral Resilience?mentioning
confidence: 99%
“…Recently, it has been shown that climate change is likely to affect nitrogen-fixing microorganisms in general and cyanobacteria in particular (Singh et al 2010;Santos et al 2014). Through the application of modern molecular phylogenetic approaches, we are beginning to better understand microbial functionality in Polar Regions.…”
Section: Nitrogen Cyclingmentioning
confidence: 99%
“…In these cases, changes in the coral‐associated bacterial community composition were interpreted as detrimental. Accordingly, changes in bacterial community structure or activity may be either beneficial or deleterious, depending on the environmental context (Ainsworth & Gates, 2016; Pogoreutz, Rädecker, Cárdenas, Gärdes, Voolstra, et al., 2017; Pogoreutz, Rädecker, Cárdenas, Gärdes, Wild, et al., 2017; Rädecker et al., 2015, 2017; Santos et al., 2014). …”
Section: Introductionmentioning
confidence: 99%